Integrated Model to Reduce the Maneuver Time of the Harvester and Infield Wagon in Sugarcane Harvest - Corrêa, Lígia Negri [UNESP]; dos Santos, Adão Felipe; Furlani, Carlos Eduardo Angeli [UNESP]; Rolim, Glauco de Souza [UNESP]; Vieira, Igor Cristian de Oliveira [UNESP]; dos Santos Silva, Breno [UNESP]; Siansi, Frederico Luiz [UNESP]; da Silva, Rouverson Pereira [UNESP] (MDPI, 2025)
This study aims to enhance the efficiency of mechanized sugarcane (Saccharum spp.) harvesting by optimizing the maneuvers of the auxiliary vehicle (infield wagon) operating in tandem with the harvester. The optimization focuses on increasing productivity and reducing soil compaction in high-traffic maneuver areas. A comprehensive three-year experimental study was conducted in agricultural fields at a Brazilian mill, where extensive field data and economic parameters were collected to simulate and compare maneuvering techniques on both flat and sloped terrain. To evaluate the synchronization between the harvester and the infield wagon under non-optimized scenarios, a Maneuver Simultaneity Index (MSI) was developed. The results demonstrated that the optimized “P-optimized” technique, which utilizes dedicated maneuvering spaces, significantly increased economic returns per hour worked by reducing maneuver times across various terrain types. Additionally, fuel consumption decreased with the adoption of the optimized maneuver pattern, leading to lower operational costs and reduced environmental impact. These findings highlight the economic and operational feasibility of optimizing maneuver patterns, particularly in flat areas, and provide a sustainable framework adaptable for improving efficiency and productivity in diverse mechanized agricultural operations.
Keywords: field efficiency; maneuver optimization; mechanized harvesting; soil compaction; sugarcane